Adding the West-African riverine component: Revision of the Recent freshwater snails belonging to Pseudocleopatra Thiele, 1928 (Caenogastropoda, Cerithioidea, Paludomidae) - Neiber, Marco T.; Kahl, Sandra M.; Wiggering, Benedikt; Glaubrecht, Matthias (Zootaxa, 2019)
While Africa’s lacustrine gastropod fauna, in particular of Lake Tanganyika, has received much attention, the continent’s riverine malacofauna has long been neglected. Pseudocleopatra is a relatively poorly known paludomid gastropod genus with species found throughout the lower reaches of the West African Volta and Congo rivers. In the course of ongoing systematic revisions of African paludomids, we present here a morphometric analysis and revision of the recent species assigned to the genus, i.e., P. togoensis, P. voltana, P. dartevellei and P. bennikei, to improve taxonomic acuity for this group. We use available museum material for geometric morphometrics, multivariate ratio analysis and comparisons of radular and opercular characters. Our results demonstrate that the four recent species of Pseudocleopatra are clearly distinguishable on the basis of ratios of shell measurements as well as radular and opercular characters. Pseudocleopatra has generic-level synapomorphies including: concentric opercula with relatively large paucispiral nuclei, and rachidian radular teeth with usually 13–20 cusps. On the basis of this characterisation, the nominal species Cleopatra broecki is transferred to Pseudocleopatra. Additionally, the nominal taxon P. bennikei is synonymized with P. broecki n. comb. The phylogenetic relationships of Pseudocleopatra are currently unknown, but the observed tendency of some fossil taxa assigned to Pseudocleopatra towards thalassoidism, i.e., the resemblance to marine gastropods, has led to the hypothesis that some of the thalassoid endemics in Lake Tanganyika may have originated from or be related to Pseudocleopatra. Should this hypothesis be correct, which is in need of testing by molecular genetic methods when suitable samples become available, Pseudocleopatra may play a crucial role in understanding of the evolution of thalassoidism in African Paludomidae.